Producción intensiva de Diatraea saccharalis en dietas artificiales, para cría de su parasitoide Cotesia flavipes, en condiciones de laboratorio - Gómez Criollo, Ismael Alexander (2022)
Through the elaboration of 3 artificial diets, the aim is to increase the production of Diatraea saccharalis larvae under laboratory conditions, in order to be used for mass breeding as hosts of the biological controller Cotesia flavipes. The research was carried out at the Catamayo Agricultural and Commercial Company. AGROCATSA, located in the province of Loja, canton Catamayo, with the objective of evaluating the nutritional quality of 3 different artificial diets for the production of Diatraea saccharalis and determining the life cycle of the screwworm Diatraea saccharalis and its parasitoid Cotesia flavipes subjected to the diets artificial under laboratory conditions. A completely randomized experimental design (DCA) with three treatments and ten repetitions was used. The results indicated that diet 1 was the one that showed the best alternative when increasing the number of D. saccharalis larvae, due to its composition of proteins, carbohydrates and vitamins that act as growth factors, these cover the nutritional needs and decreases the risks of diseases due to contamination of pathogens in D. saccharalis larvae, in the same way in the percentage of parasitism of C. flavipes in D. saccharalis larvae, diet 1 presented better behavior since a total number of 4730 individuals was obtained C. flavipes adults. Diet 1 had a positive influence on the life cycle of the individuals, rapidly reducing the development of the life cycle of D. saccharlis (30 days) as well as C. flavipes (11 days) in larvae of D. saccharlis, which allows us to carry out different studies in a faster and more efficient way. Key words: Diatraea saccharalisse, Cotesia flavipes.